Dendritic cells transfected with scFv from Mab 7.B12 mimicking original antigen gp43 induces protection against experimental Paracoccidioidomycosis - Ferreira, Karen Spadari (2011)
Paracoccidioidomycosis (PCM), endemic in Latin America, is a progressive systemic mycosis caused by Paracoccidioides brasiliensis (P. brasiliensis), which primarily attacks lung tissue. Dendritic cells (DCs) are able to initiate a response in naı¨ve T cells, and they also participate in Th-cell education. Furthermore, these cells have been used for therapy in several disease models. Here we transfected DCs with a plasmid (pMAC/PS-scFv) encoding a single chain variable fragment (scFv) of an anti Id antibody that is capable of mimicking gp43, the main antigenic component of P. brasiliensis. First, Balb/c mice were immunized subcutaneously with pMAC/PS-scFv and, after seven days, scFv protein was presented to the regional lymph nodes cells. Moreover, we showed that the DCs transfected with scFv were capable of efficiently activating proliferation of total lymph node cells and inducing a decrease in lung infection. Therefore, our results suggested that the use of scFvtransfected DCs may be a promising therapy in the paracoccidioidomycosis (PCM) model.